Kaplan and Marti on definite descriptions - E. V. Borisov (Омский научный вестник: Серия "Общество. История. Современность")
Donnellan’s distinction between referential and attributive uses of definite descriptions gave rise to controversy between semantic and pragmatic accounts of referentially used descriptions. Kaplan adumbrated and Marti elaborated in detail a semantic account that assimilates referentially used definite descriptions with proper names in the sense of the theory of direct reference. I argue that the evidence Kaplan-Marti theory relies on is inappropriate, and conclude that KaplanMarti theory has no advantage over the pragmatic account of referential use in Donnellan’s sense.